2015
DOI: 10.4103/1817-1737.160840
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between pentraxin-3 and endothelial dysfunction in obstructive sleep apnea syndrome

Abstract: BACKGROUND AND AIM:Obstructive sleep apnea syndrome (OSAS) is an independent risk factor for cardiovascular disease. Recent studies showed endothelial dysfunction and pentraxin-3 both of an early marker for development of cardiovascular disease. The aim of the study was to evaluate the relationship between severity of OSAS and endothelial dysfunction and inflammatory markers including pentraxin-3 and high-sensitivity C-reactive protein (hs-CRP).METHODS:This was a cross-sectional study in which patients who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
4
20
0
Order By: Relevance
“…OSAS is a clinical condition characterized by recurrent upper airway obstruction during sleep and associated with increased systemic inflammatory markers. The association between inflammation and the presence of sleep‐disordered breathing has been shown in many studies . In the current study, we found that patients with OSAS have elevated plasma PTX‐3, IL‐33 and sST2 levels.…”
Section: Discussionsupporting
confidence: 69%
“…OSAS is a clinical condition characterized by recurrent upper airway obstruction during sleep and associated with increased systemic inflammatory markers. The association between inflammation and the presence of sleep‐disordered breathing has been shown in many studies . In the current study, we found that patients with OSAS have elevated plasma PTX‐3, IL‐33 and sST2 levels.…”
Section: Discussionsupporting
confidence: 69%
“…Inflammation may be the explanation for such an association. In a recent study, we showed an independent strong association between inflammation, endothelial dysfunction and OSA . The last explanation may be the increase in vascular adhesion molecules.…”
Section: Discussionmentioning
confidence: 54%
“…New biomarkers showing OSA prognosis will be of value especially for future CV risk stratification. Various underlying mechanisms including oxidative stress, inflammation, reduced plasma levels of nitrite and nitrate, increased lipid peroxidation, sympathetic activation, insulin resistance and reduced antioxidant capacity are thought to be involved in OSA pathogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase of sympathetic nervous system (SNS) activity, increase of vascular resistance, activation of the renin-angiotensin-aldosterone system, and increase of arterial stiffness following sleep loss and hypoxemia are some involving factors in this type of hypertension [25][26][27]. In addition, patients that suffer from OSA have some degrees of endothelial dysfunction [28] that may be another predisposing factor for hypertension. However, this effect cannot be attributed to the hyperactivity of hypothalamic-pituitary-adrenal (HPA) axis [24,29].…”
Section: Discussionmentioning
confidence: 99%